2023
DOI: 10.3390/life13010190
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Countermovement Jump: What Should We Report?

Abstract: The purpose of the present study was (i) to explore the reliability of the most commonly used countermovement jump (CMJ) metrics, and (ii) to reduce a large pool of metrics with acceptable levels of reliability via principal component analysis to the significant factors capable of providing distinctive aspects of CMJ performance. Seventy-nine physically active participants (thirty-seven females and forty-two males) performed three maximal CMJs while standing on a force platform. Each participant visited the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 39 publications
4
31
0
Order By: Relevance
“…Collegiate men's basketball players underwent a lateral jump task off a three-dimensional force plate. To identify predictors of lateral jump performance, variables that had been previously used to predict vertical CMJ performance [6,27] were computed from the force-time curves of the force plate outputs during the task and ultimately correlated to achieved lateral distance. Metrics included peak ground reaction force, average concentric force, and eccentric braking rate of force development, jump duration, eccentric phase duration, and eccentric to total duration ratio.…”
Section: Experimental Approach To the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Collegiate men's basketball players underwent a lateral jump task off a three-dimensional force plate. To identify predictors of lateral jump performance, variables that had been previously used to predict vertical CMJ performance [6,27] were computed from the force-time curves of the force plate outputs during the task and ultimately correlated to achieved lateral distance. Metrics included peak ground reaction force, average concentric force, and eccentric braking rate of force development, jump duration, eccentric phase duration, and eccentric to total duration ratio.…”
Section: Experimental Approach To the Problemmentioning
confidence: 99%
“…Velocity and displacement can then be used to distinguish the eccentric and concentric phases of the jump motion [2-4, 6, 11, 13, 14], both of which represent a fundamental component of the muscular stretch shortening cycle (SSC). Many different metrics can be derived from the displacement and velocity curves and they allow for evaluation of specific components of an athlete's SSC [11,27]. Metrics that have been identified as predictors of task performance can then be targeted for specialized modifications.…”
Section: Introductionmentioning
confidence: 99%
“…The selection of the force-time metrics studied in the present investigation was founded on previous research reports, including variables with a considerable level of reliability and practical applicability for sport scientists and strength and conditioning practitioners (1,12,19). Force-time metrics examined during the eccentric phase of CVJ were as follows: braking phase duration and impulse, eccentric duration, peak velocity, mean and peak force, and mean and peak power.…”
Section: Variablesmentioning
confidence: 99%
“…When predicting adult height of males between 4 and 17.5 years, the median error associated with the Khamis-Roche method is 2.2 cm (15). The standing height of participant's biological parents was collected by a member of the research team, or where collection was not possible, self-reported by the parents and subsequently adjusted for overestimation using the equation provided by Epstein et al (9) (Equation [1]).…”
Section: Anthropometry and Maturity Statusmentioning
confidence: 99%
“…An awareness of this developmental phenomenon is important as it is recommended that training volumeloads are modified to avoid excessive stress and to facilitate the re-learning of previously acquired skills and movement patterns (20). Despite previous research highlighting these patterns of development during growth and maturation, monitoring JH alone is limited as it does not describe jump strategy (1,5). Therefore, expanding analyses to include braking ("eccentric") and propulsion ("concentric") phase variables has been recommended to simultaneously monitor jump strategy as well as outcome (5,6,17).…”
Section: Introductionmentioning
confidence: 99%